2020
DOI: 10.1002/jrs.6005
|View full text |Cite
|
Sign up to set email alerts
|

Application of Raman spectroscopy for identification of rinneite (K3NaFeCl6) in inclusions in minerals

Abstract: Solid daughter phases in fluid and salt melt inclusions in minerals provide important clues to characterization of mineral-forming processes. The analysis of the fluid inclusions often requires the exposure of the daughter minerals. Rinneite (K 3 NaFeCl 6), which is a hygroscopic mineral, decomposes in air and cannot thus be identified by conventional methods. A combined approach has been applied for investigation of synthetic and natural rinneite to acquire its diagnostic Raman spectrum for a nondestructive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…[14] A number of unusual minerals in kimberlites of Udachnaya-East pipe have been described and characterized. [15][16][17] Current work continues a series of Raman characterizations of minerals [18,19] within chloride segregations as opposed to descriptions of alkali compounds in kimberlite groundmass and secondary inclusions in olivin.…”
Section: Introductionmentioning
confidence: 99%
“…[14] A number of unusual minerals in kimberlites of Udachnaya-East pipe have been described and characterized. [15][16][17] Current work continues a series of Raman characterizations of minerals [18,19] within chloride segregations as opposed to descriptions of alkali compounds in kimberlite groundmass and secondary inclusions in olivin.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between magmas and evaporites, including the incorporation of sedimentary pore fluids (e.g., brines), can significantly increase the volatile contents of magmas (Heimdal et al, 2019), as has been suggested to explain some high chlorine contents of melt inclusions in Siberian Traps Large Igneous Province rocks (Sobolev et al, 2009;Black et al, 2012). Previous studies have described the textures and skarn mineralogy produced at the contact between dolerites and evaporites in the Nepa River region (Grishina et al, 1991;Grishina et al, 1992;Istomin et al, 2000;Mazurov et al, 2007;Polozov et al, 2016;Grishina et al, 2018;Grishina et al, 2020). Evidence for interactions with magmas may be retained in the basalts and the contact aureole in the salts.…”
Section: Introductionmentioning
confidence: 94%
“…This type of inclusion occurs together with vapor-rich inclusions as primary assemblages and secondary trails. The translucent crystals in these inclusions are halite (NaCl), sylvite (KCl), Rinneite (K3NaFeCl6; Grishina et al, 2020), Javorieite (KFeCl3; Koděra et al, 2017), and anhydrite (Fig. DR5A).…”
Section: Figure Dr5 Raman Spectra Of Phases In Melt Inclusions From C...mentioning
confidence: 99%